Invasive aspergillosis in solid organ transplant patients: diagnosis, prophylaxis, treatment, and assessment of response - Neofytos, Dionysios; Garcia-Vidal, Carolina; Lamoth, Frédéric; Lichtenstern, Christoph; Perrella, Alessandro; Vehreschild, Jörg Janne (BMC infectious diseases, 2021)
Invasive aspergillosis (IA) is a rare complication in solid organ transplant (SOT) recipients. Although IA has significant implications on graft and patient survival, data on diagnosis and management of this infection in SOT recipients are still limited.
Gesehen am 11.07.2021